2019
DOI: 10.3390/cells8060559
|View full text |Cite
|
Sign up to set email alerts
|

Viral Appropriation: Laying Claim to Host Nuclear Transport Machinery

Abstract: Protein nuclear transport is an integral process to many cellular pathways and often plays a critical role during viral infection. To overcome the barrier presented by the nuclear membrane and gain access to the nucleus, virally encoded proteins have evolved ways to appropriate components of the nuclear transport machinery. By binding karyopherins, or the nuclear pore complex, viral proteins influence their own transport as well as the transport of key cellular regulatory proteins. This review covers how viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 195 publications
(232 reference statements)
1
21
0
Order By: Relevance
“…The stimulus and mechanistic details of virus uncoating remain largely concealed. Virus infection in eukaryotic cells often depends on the nuclear transport machinery ( Cohen et al, 2011 ; Matreyek and Engelman, 2013 ; Tessier et al, 2019 ). Recent studies have shown a direct role of Trn1 in virus uncoating ( Fernandez et al, 2019 ; Miyake et al, 2019 ; Carlon-Andres et al, 2020 ; Yamauchi, 2020 ).…”
Section: Moonlighting Functions Of Transportin-1mentioning
confidence: 99%
“…The stimulus and mechanistic details of virus uncoating remain largely concealed. Virus infection in eukaryotic cells often depends on the nuclear transport machinery ( Cohen et al, 2011 ; Matreyek and Engelman, 2013 ; Tessier et al, 2019 ). Recent studies have shown a direct role of Trn1 in virus uncoating ( Fernandez et al, 2019 ; Miyake et al, 2019 ; Carlon-Andres et al, 2020 ; Yamauchi, 2020 ).…”
Section: Moonlighting Functions Of Transportin-1mentioning
confidence: 99%
“…By coevolving with eukaryotic hosts, viral pathogens have developed diverse mechanisms to usurp this important and highly coordinated pathway. These include mimicry of cellular NLSs by viral proteins and manipulation of these host factors at the molecular level (9).…”
mentioning
confidence: 99%
“…Through a highthroughput drug-screening approach, ivermectin was also identified as a general inhibitor of Imp-␣/␤1-mediated nuclear import (31). Several recent studies have explored ivermectin as a means of abrogating nuclear localization of viral proteins and as an inhibitor of viral replication (9). Several RNA viruses, including human immunodeficiency virus (HIV), dengue virus (DENV), and Hendra virus (HeV), were potently inhibited in vitro by ivermectin (32)(33)(34).…”
mentioning
confidence: 99%
“…That the INM STING pool can mobilize to translocate to the ONM through the peripheral channels of the NPC may reflect a backup mechanism to signal IIR responses using the peripheral NPC channels when viruses inhibit central channel transport. Viruses often target the central channel of the NPCs to either block transport or to usurp it so that virus transcripts are preferentially transported over host-directed transport 71,72,73,74 , but the peripheral channels are normally used for membrane protein transport 38,42,43,75 so that STING as a multi-spanning transmembrane protein could bypass this block to signal IIR. This does not preclude the well-established STING signaling cascades from the ER/Golgi compartment normally using the central channel of the NPC -indeed IRF3 is known to translocate through the NPC central channel 76,77 , but our findings of increased STING mobility and nucleo-cytoplasmic shuttling during IIR through the peripheral NPC channels suggest that STING may provide a backup system for activating IIR when central channel transport is disrupted.…”
Section: Discussionmentioning
confidence: 99%